2020
DOI: 10.3390/ijms21051843
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Cytoplasmic IgE-Positive Mast Cells in Eosinophilic Chronic Rhinosinusitis

Abstract: Cross-linking of antigen-specific IgE bound to the high-affinity IgE receptor (FcεRI) on the surface of mast cells with multivalent antigens results in the release of mediators and development of type 2 inflammation. FcεRI expression and IgE synthesis are, therefore, critical for type 2 inflammatory disease development. In an attempt to clarify the relationship between eosinophilic chronic rhinosinusitis (ECRS) and mast cell infiltration, we analyzed mast cell infiltration at lesion sites and determined its cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
(34 reference statements)
1
8
0
Order By: Relevance
“…Clinically, it is noteworthy that we found that the postoperative recurrence rate of severe ECRS was significantly higher than that of less severe ECRS (see Table 2). Gion et al recently compared characteristics of patients showing different ECRS severity, 21 and their observations were comparable to what we report here. For example, serum IgE levels, the proportion of eosinophils in peripheral blood, and comorbidity with asthma in severe ECRS were higher than those values seen in less severe ECRS.…”
Section: Discussionsupporting
confidence: 92%
“…Clinically, it is noteworthy that we found that the postoperative recurrence rate of severe ECRS was significantly higher than that of less severe ECRS (see Table 2). Gion et al recently compared characteristics of patients showing different ECRS severity, 21 and their observations were comparable to what we report here. For example, serum IgE levels, the proportion of eosinophils in peripheral blood, and comorbidity with asthma in severe ECRS were higher than those values seen in less severe ECRS.…”
Section: Discussionsupporting
confidence: 92%
“…Mast cells . Two studies showed that mast cells are significantly increased in NPs and primarily accumulate in the epithelium 822,823 1472 . Type 2 cytokines, IL‐5, IL‐13, and IL‐4, are secreted by mast cells, Th2 cells and group 2 ILCs 1473 and therefore mast cells may enhance Th2 inflammation 1469 …”
Section: Chronic Rhinosinusitis With Nasal Polyps (Crswnp)mentioning
confidence: 99%
“…Here we have analyzed the inflammatory modulations due to dupilumab treatment, as well as modulation of miRNAs expression, to identify new prognostic biomarkers. It was well demonstrated that increased IgE and IL-8 concentrations may be found in patients with CRSwNP stimulating multiple inflammatory pathways [ 23 , 24 ]. Indeed, IL-8 plays a crucial role in the inflammatory processes acting as a chemotactic factor for neutrophils and lymphocytes, as angiogenic factor, as well as tumor progression [ 25 , 26 , 27 ], and an IL-8-dominant inflammatory profile is frequently found in patients with CRSwNP [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%